The Value and Function of Public Policy in Public Management - Choi, Chingyu (International Journal of Social Sciences and Public Administration, 2024)
As a mechanism driving the development and management of modern society, public policy has irreplaceable value and functionality. This article first explores the value of public policy in public management, including how it promotes the resolution of social issues, optimizes resource allocation, and promotes social fairness and justice. Secondly, the article lists the functions of public policy in public management and finally discusses how to implement public policy practices in public management.